Erupted rootless type III dense in dente (dilated odontoma) masquerading as peripheral gingival pathosis. (21st February 2013) - Ide, F.; Ito, Y.; Muramatsu, T.; Saito, I.; Mishima, K.
Abstract Dense in dente, also known as dense invaginatus or dilated odontoma, is a developed malformed tooth and usually does not pose a diagnostic challenge. Described here is a unique case in which a rootless type III dense in dente (dilated odontoma) between the lower deciduous molars in a 2‐year‐old girl emerged through the gingiva mimicking a peripheral developing odontoma. At the time of examination, neither anchored in bone nor associated with an underlying un‐erupted tooth. The small size, the superficial position in the growing mandible, the absence of the overlying bone and the physiologic eruptive movement of the neighbouring teeth may predispose the present rootless dense in dente to erupt in the gingiva.